De collectie van het Stedelijk Museum 1963-1973. - de Wilde, Edy (Amsterdam : Stedelijk Museum Amsterdam, 1977)
Akkerman, Ben ; Alma, Peter ; van Amen, Woody ; Appel, Karel ; Arman ; Armando ; Baertling, Olle ; Bakker, Douwe Jan ; Baldessari, John ; Baljeu, Joost ; Balth, Carel ; Barbeau, Marcel ; Barry, Robert ; Baruchello, Gianfranco ; Bazaine, Jean ; Bell, Larry ; Ben ; Benner, Gerrit ; Beres, Jerzy ; Berghuis, Jaap ; Bernstein, Richard ; Beutener, Jan ; Beuys, Joseph ; Bissière, Roger ; Boetti, Alighiero ; Boezem, Marinus ; van Bohemen, Kees ; Bouws, Donald ; Brands, Eugène ; Brusse, Mark ; Bury, Pol ; Camesi, Gianfredo ; Casimir ; Castellani, Enrico ; Christo ; Claassen, Johan ; Constant ; Cooper, Ron ; Copley, William ; Corneille ; Couzijn, Wessel ; Dado, Miodrag ; Darboven, Hanne ; Deckwitz, Franz ; Defesche, Pieter ; Dekkers, Ad ; Dekkers, Ger ; Dewitt, Floyd ; Dibbets, Jan ; Diederen, Jef ; Dill, Guy ; Dine, Jim ; van Doesburg, Theo ; Domela, César ; de Dominicis, Gino ; Dorazio, Piero ; Drion, Wim ; Dubuffet, Jean ; Duffaut, Prefete ; Van den Eerenbeemt, Gérard L.G.M. ; Elias, Etienne ; van Elk, Ger ; van den Ende, Jaap ; Engelman, Martin ; Engels, Pieter ; Etienne-Martin, Henri ; Ferdi ; Fernhout, Edgar ; Flanagan, Barry ; Riverhead (New York) ; Fontana, Lucio ; Francis, Sam ; Freijmuth, Alphons ; Fulton, Hamish ; Gallizio, Pinot ; van Genk, Willem ; Gentils, Vic ; Gerritse, Kees ; Gilbert & George ; Gnoli, Domenico ; Van Goethem, Jan ; van Golden, Daan ; Gorin, Jean ; Grosman, John ; de Haas, Els ; Henderikse, Jan ; Henneman, Jeroen ; Hofkunst, Alfred ; Hollenbach, Hans ; Holt, Friso ten ; Holtrop, Riemko ; Huebler, Douglas ; Indiana, Robert ; Israels, Isaac ; Johansson, Albert ; Johns, Jasper ; Jones, Allen ; Joosten, Egbert ; Jorn, Asger ; Kacere, John ; Keizer, Jerry ; Kelly, Ellsworth ; Kienholz, Edward ; Kitaj, R.B. ; Klein, Yves ; etc.
Tent. 1963-1973 p. 82-107
Nederlands & Engels
boek